Generalized sums for characters and their applications to the reciprocity laws - Reshetukha, I. V.; Решетуха, И. В. (Institute of Mathematics, NAS of Ukraine, 1971)
В работе приводится новое доказательство квадратичного и кубического законов взаимности с применением сумм для характеров.